Are Zeno’s Arguments Unsound Paradoxes? - Calenda, Guido (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2013)
Zeno’s arguments are generally regarded as ingenious but downright unsound paradoxes, worth of attention mainly to disclose why they go wrong or, alternatively, to recognise them as clever, even if crude, anticipations of modern views on the space, the infinite or the quantum view of matter. In either case, the arguments lose any connection with the scientific and philosophical problems of Zeno’s own time and environment. In the present paper, I argue that it is possible to make sense of Zeno’s arguments if we recognise that Zeno was indeed a close follower of Parmenides, who wanted to show that, if the plurality of beings existed, then various absurd consequences would follow. When doing so, he intended to highlight the compact and inarticulate nature of the being, and the human character of the system of world partitions producing the entities and the objects on which our knowledge is based.
Keywords: Eleatism; Zeno; Paradoxes; Ontology